2012
DOI: 10.4103/0975-3583.91592
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of glimepiride (Amaryl) and repaglinide (novoNorm) on atherosclerosis progression in high cholesterol-fed male rabbits

Abstract: Background:Atherosclerosis is an inflammatory disease of the blood vessel wall, characterized in early stages by endothelial dysfunction, recruitment and activation of monocyte/macrophages. Glimepiride is one of the third generation sulphonylurea drugs, useful for control of diabetes mellitus type two and it may exert anti inflammatory activity, by induction of nitric oxide production or through selective suppression of the cyclooxygenase pathway. Repaglinide is a new hypoglycemic agent, and a member of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
3
6
0
Order By: Relevance
“…These findings coincided with those of Hadi et al [21]. These findings coincided with those of Hadi et al [21].…”
Section: Morphometric Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings coincided with those of Hadi et al [21]. These findings coincided with those of Hadi et al [21].…”
Section: Morphometric Resultssupporting
confidence: 92%
“…This was found previously by Hadi et al [21] who stated that atherosclerosis is an inflammatory disease of the blood vessel wall, characterized during early stages by endothelial dysfunction and activation of monocytes/macrophages. A collection of foam cells was seen in the subendothelial region and in the media during light microscopic examination.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, it is reasonable that when serum LDL-C levels are reduced, levels of sd-LDL, which constitutes LDL, are also reduced. It has also been reported that glimepiride has antiatherosclerotic effects such as an LDL oxidation inhibitory effect [16][17][18]. However, mitiglinide/voglibose fixed-dose combination did not change serum LDL-C levels significantly, but reduced the ratio of sd-LDL to LDL, i. e., sd-LDL proportion, and increased the mean particle size of all LDL particles, which is represented by LDL-C/apoB, indicating that mitiglinide/voglibose fixed-dose combination has an effect of inhibiting LDL-induced arteriosclerosis, an effect different from that of glimepiride [13,19].…”
mentioning
confidence: 99%
“…In clinical practice, exogenous cholesterol is interesting since modifying eating habits can help lower cholesterol leveles. Some research was carried out on laboratory animals to evaluate hypercholesterolemia as follows: a) on genetically modified animals (endogenous) (Song G. et al 2011, Dworschak M et al 2005; b) on high-cholesterol-fed animals (exogenous) (Bulgarelli A et al 2011;Hadi NR et al 2012); c) combining both (endogenous and exogenous) (Ishibashi S et al 2011, Scalia R et al 2001…”
mentioning
confidence: 99%